Manfaat Sumber Data Arkeologi (Epigrafi) Sebagai Acuan Penelusuran Harijadi Suatu Daerah - Djoko Dwiyanto (Balai Arkeologi Yogyakarta, 1994)
In fact, the development of archaeological research in Indonesia is not in line with the knowledge and perception of the wider community about that field of science. On the one hand, research shows a very rapid development, while on the other hand the community always considers that the archaeological study area is limited to areas and temples, or recently limited to skulls and fossils. This is due, among other things, to the limited scientific publications that can be enjoyed by the wider community, even if their distribution is very limited. Another reason, especially is the lack of public interest and attention to the field of archeology in particular and the field of culture in general, which is considered unable to directly provide material benefits.